The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1186/1471-2350-14-102
|View full text |Cite
|
Sign up to set email alerts
|

Aneuploidy in neuroblastoma tumors is not associated with inactivating point mutations in the STAG2 gene

Abstract: BackgroundChromosomal instability is a hallmark of human cancer caused by errors in mitotic control and chromosome segregation. STAG2 encodes a subunit of the cohesion complex that participates in mitotic chromatid separation and was recently found to show low expression and inactivating mutations in Ewing’s sarcoma, melanoma and glioblastoma.In the childhood tumor neuroblastoma (NB) segmental chromosomal alterations are associated with poor prognosis whereas tumors displaying whole chromosome gains and losses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…ATRX is part of a complex responsible for deposition of H3.3 variants at naked DNA and, hence, widely affects the expression of different genes (44). In addition, mutations in other epigenetic components, including EZH2 (45), stromal antigen 2 ( STAG2 ) (46), and AT-rich interaction domain 1AB ( ARID1A/B ) (47), are found in neuroblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…ATRX is part of a complex responsible for deposition of H3.3 variants at naked DNA and, hence, widely affects the expression of different genes (44). In addition, mutations in other epigenetic components, including EZH2 (45), stromal antigen 2 ( STAG2 ) (46), and AT-rich interaction domain 1AB ( ARID1A/B ) (47), are found in neuroblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the loss of expression of STAG2 has been reported in colorectal, gastric and prostate carcinomas; however there are few mutations in STAG2 in these carcinomas . Similarly, somatic mutation of STAG2 is rare in acute leukemias (Chung et al, 2012) and neuroblastoma tumors (Djos et al, 2013). In contrast, in myeloid neoplasms, recurrent mutations and deletions have been detected in another study (Kon et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…EP300 is mutated in a small proportion of Rubinstein-Taybi syndrome cases [ 94 ] and in cancers exhibiting instable genomes, which can be a result of alterations to chromatin-remodeling [ 95 ]. Although inactivating point mutations in STAG2 are not likely to be directly related to aneuploidy [ 96 ], more recent studies have shown that frequent sequence variations are inversely related to chromosomal copy number changes [ 97 ]. CDK6 mutations causing clinical conditions and several cancers are involved in processes related to aneuploidization [ 98 , 99 ].…”
Section: Resultsmentioning
confidence: 99%